Correlation of pathogenic effects of laryngopharyngeal reflux and bacterial infection in COME of children. (4th May 2021) - Lei, Lei; Yu, Zhao; Yu, Rong; Yang, Hui; Zou, Jian; Ren, Jianjun; Zhang, Jie; Zhong, Dalin
Abstract: Background: Bacteria infection and laryngopharyngeal reflux (LPR) were believed the important pathogenesis of chronic otitis media with effusion (COME). But no study researched the relationship between them on COME. Aims: To confirm bacterial could arrive middle ear through LPR and produced acid metabolites to activate the pepsinogen of LPR causing COME. Material and methods: Children (65) diagnosed COME with 122 middle ear effusions were included in COME group. Children (22) with congenital/acquired profound deafness with 22 middle ear lavage were included in CI group. Pepsin A concentration in the effusion and lavage fluid were measured. The DNA of the bacteria, IL-8 and TNF-α in the effusion were detected. Results: The average concentration of pepsin A in the effusions and lavage were 176.65 ± 242.09 and 19 ng/ml. Bacterial infection rates were 75.76% and 24.24% in the pepsin A(+) and pepsin A(−) patients. In the bacterial (+), the patients of pepsin A(+) was 4.33 times higher than those of pepsin A(−). TNF-α in pepsin A(+) was higher than that in pepsin A(−). TNF-α and IL-8 were higher in bacteria(+) than those of bacteria(−). Conclusions: Bacterial infection and LPR might act in synergy in the pathogenesis of COME. Significance: First time to propose LPR and bacterial infection might work synergistically to cause COME.